PENERAPAN PROJECT-BASED LEARNING DENGAN STANDAR PROJECT MANAGEMENT BODY OF KNOWLEDGE - Jariyah, Ainun (Infotech: Journal of Technology Information, 2019)
The Republic of Indonesia has completed competency standards for tertiary institutions which will be approved and developed in the 21st century. The problem in this research is the use of monotonous student lecture methods that are less active in the learning process. This causes students to be passive, bored, lazy, and less enthusiastic in learning. An appropriate learning model is needed to enhance the expected learning where one of them is Project Based Learning (PBL). The purpose of this study is for students to understand the problem and develop critical thinking skills. PBL has been widely adopted and used in various fields because the learning model not only gives students knowledge, but also directs students to facilitate their understanding in real life relationships. Data collection methods are used to complete the library by updating and using two types of sources. The Project Based Learning learning model by studying the Project Management Agency (PMBOK) can improve learning outcomes, increase student activity, skills, knowledge, and abilities in accordance with 21st century challenges.